2020
DOI: 10.1186/s42358-020-00132-w
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps muscle properties in rheumatoid arthritis: insights about muscle morphology, activation and functional capacity

Abstract: Background Rheumatoid arthritis (RA) is an inflammatory and chronic autoimmune disease that leads to muscle mass loss and functional capacity impairment, potentiated by physical inactivity. Despite evidences demonstrate neuromuscular impairments in RA patients, aging effects may have masked the results of similar previous studies. The aim of study was to verify (i) the effects of RA on functional capacity and muscle properties in middle-aged patients and (ii) the association between age, clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 45 publications
2
10
4
Order By: Relevance
“…Our findings of mean VL muscle thickness and VL pennation angle were higher. However, RA patients of the Blum et al (2020) study [34] had moderate mean disease activity, while our RA patients had low disease activity. In fact, our VL muscle thickness findings (1.61 ± 0.43 cm) were lower than those from the healthy group in this same study [34].…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…Our findings of mean VL muscle thickness and VL pennation angle were higher. However, RA patients of the Blum et al (2020) study [34] had moderate mean disease activity, while our RA patients had low disease activity. In fact, our VL muscle thickness findings (1.61 ± 0.43 cm) were lower than those from the healthy group in this same study [34].…”
Section: Discussioncontrasting
confidence: 53%
“…There are limited data on muscle morphology assessment by ultrasound in RA patients. Blum et al (2020) [34] recently found mean muscle thickness and pennation angle in patients with RA of 1.37 ± 0.34 cm and 8.65 ± 2.36 • , respectively. Our findings of mean VL muscle thickness and VL pennation angle were higher.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations